Unmasking climate vulnerability in Africa: the role of CO2 and CH4 emissions on rising temperatures and sea levels - Thanula Gunaratne; Sajani Liyanage; Chamathka Punchihewa; Shamah Badurdeen; Ruwan Jayathilaka (Humanities & Social Sciences Communications)
Abstract Climate change influenced by anthropogenic emissions is a global occurrence affecting the Mean Surface Temperature (MST) and Mean Sea Level (MSL) patterns. The African continent contributes to the lowest Greenhouse Gas (GHG) emissions globally. However, GHG emissions, particularly Carbon Dioxide (CO2) and Methane (CH4) emission patterns, show a continuous increase in the African region, reflecting the importance of practising economic growth in the continent with sustainable environmental policies to meet future global climate targets. Given Africa’s increasing emissions and the continent’s vulnerability to climate change, this study contributes to the existing literature by assessing the continental and country-wise impact of CO2 and CH4 emissions on MST and the resulting impact on MSL through Fixed Effect (FE) panel estimation and Simple Linear Regression (SLR). The research employs data from 1993 to 2020 for fifty-four African countries. The study’s main findings show that CO2 and CH4 positively impact MST at a 1% significance level, and MST positively impacts MSL at a 5% significance level. This study focuses on continent-specific and country-specific emissions and their impacts and proposes policy measures to mitigate the emissions in the African continent.